India - Fontes, Justine; Fontes, Ron. (New York : Children's Press, 2003)
Explores the history, geography, economy, people, culture, and other aspects of India, featuring a topic for each letter of the alphabet.
Animals -- Buildings -- Cities -- Dress -- Exports -- Food -- Government -- History -- Important people -- Jobs -- Keepsakes -- Land -- Map -- Nation -- Only in India -- People -- Question -- Religion -- School & sports -- Transportation -- Unusual places -- Visiting the country -- Window to the past -- X-tra special things -- Yearly festivals -- Zeera.
Includes bibliographical references (p. 39) and index.
4.6
K-3
Keywords: India -- Juvenile literature; India; India; India